Design and Performance Analysis of a Spiral-Type Corn Sheller Machine for Small-Scale Farmers - R, Rildiwan; Allen, Rio Valery; Zulnadi, Zulnadi; Melly, Sandra; Ilhamsyah, Ilhamsyah; Ihsan, Muhammad; Fadli, Zul; Saleh, Abdurahman (The Future of Education Journal, 2026)
Corn (Zea mays) is a vital global commodity, yet traditional shelling remains a bottleneck for small-scale farmers, leading to high labor intensity and low productivity. This study aimed to design, construct, and evaluate the performance of a spiral-type corn sheller powered by a 1-HP electric motor. The performance was assessed through quantitative parameters (feeding rate, shelling capacity, and yield) and qualitative parameters (percentage of damaged and unshelled seeds). Results indicated a shelling capacity of 150 kg/h with a yield of 87%. The quantitative analysis showed 0.24% of unshelled seeds and 7% seed damage. Economic evaluation revealed a production cost of Rp 135.83/kg and a Break-Even Point (BEP) of 1,911.96 kg/year. The spiral-type mechanism effectively increases efficiency compared to manual shelling (±20 kg/h), making it a viable solution for small-scale agricultural industries.